2021
DOI: 10.1177/17534259211014252
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HMGB1 auto-Abs influence fatigue in patients with Crohn’s disease

Abstract: Fatigue is common in all chronic inflammatory and autoimmune diseases. A conceptual model for understanding the biological basis of fatigue describes it as being a part of the sickness behaviour response generated by pro-inflammatory cytokines and other mediators. We hypothesised that the pro-inflammatory high mobility group box 1 (HMGB1) protein is a fatigue-inducing molecule and that auto-Abs against HMGB1 reduce fatigue. We measured Abs against disulphide (ds) HMGB1 and fully reduced (fr) HMGB1 in plasma fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Those findings suggests that subclinical disease activity might be involved in generating fatigue by stimulating fatigue signaling pathways. Another possible factor could be that the mechanisms that downregulate inflammation and immunity might contribute to fatigue, as suggested in studies on other inflammatory diseases ( 40 43 ). In our study, a fraction of patients had shown evidence of disease activity (e.g., elevated anti-tTG-IgA and signs of villous atrophy) after the GFD.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings suggests that subclinical disease activity might be involved in generating fatigue by stimulating fatigue signaling pathways. Another possible factor could be that the mechanisms that downregulate inflammation and immunity might contribute to fatigue, as suggested in studies on other inflammatory diseases ( 40 43 ). In our study, a fraction of patients had shown evidence of disease activity (e.g., elevated anti-tTG-IgA and signs of villous atrophy) after the GFD.…”
Section: Discussionmentioning
confidence: 99%
“…EDTA-blood was centrifuged at 2800 g for 15 min at 4 °C and plasma samples stored immediately at − 80 °C in aliquots until further analysis. Based on previous experiences and findings in our laboratory regarding potential biomarkers for fatigue (Bårdsen et al 2019 , 2016 ; Kvivik et al 2021 ; Grimstad et al 2020 ; Larssen et al 2019 ; Harboe et al 2009 ) we selected a panel of relevant candidate proteins. Plasma concentrations of IL-1RA were measured by a sandwich immunoassay with electrochemiluminescence detection on a Meso ® QuickPlex SQ 120 Imager (Meso Scale Discovery, Rockville, MD).…”
Section: Methodsmentioning
confidence: 99%
“…A mechanism for regulating HMGB1 is production of autoantibodies against HMGB1. We have previously shown that high levels of anti-HMGB1 antibodies (abs) in plasma from patients with Crohn’s disease are negatively associated with high fatigue (Kvivik et al 2021 ), suggesting a protective/down-regulating role for these specific abs.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the redox state, there are three forms of HMGB1, namely, disulfide HMGB1 (ds-HMGB1), fully reduced HMGB1 (fr-HMGB1) and fully oxidized HMGB1 (ox-HMGB1) ( Frank et al, 2015 ; Kang et al, 2014 ). Ds-HMGB1 promotes inflammation and ultimately results in systemic inflammation ( Frank et al, 2016 ; Kvivik et al, 2021 ; Xiong et al, 2022 ) via binding to Toll like receptors (TLRs, e.g., TLR2 and TLR4) when cysteines at positions 23 and 45 become oxidized, while cysteine at position C106 remains in a reduced thiol state ( Yamasoba et al, 2016 ). Several studies indicate that ds-HMGB1 exacerbates neuroinflammation, resulting in anxiety, aversion and fatigue in mice or patients ( Du et al, 2022 ; Kvivik et al, 2021 ).…”
Section: Structure and Features Of Hmgb1mentioning
confidence: 99%
“…Ds-HMGB1 promotes inflammation and ultimately results in systemic inflammation ( Frank et al, 2016 ; Kvivik et al, 2021 ; Xiong et al, 2022 ) via binding to Toll like receptors (TLRs, e.g., TLR2 and TLR4) when cysteines at positions 23 and 45 become oxidized, while cysteine at position C106 remains in a reduced thiol state ( Yamasoba et al, 2016 ). Several studies indicate that ds-HMGB1 exacerbates neuroinflammation, resulting in anxiety, aversion and fatigue in mice or patients ( Du et al, 2022 ; Kvivik et al, 2021 ). Xiong et al demonstrated that ds-HMGB1 bound to myeloid differentiation protein-2 to activate NLRP3, thereby releasing inflammatory factors (e. g., TNF-α, IL-1β, and IL-10) and impairing cognitive behaviors in mice with sepsis-associated encephalopathy ( Xiong et al, 2022 ).…”
Section: Structure and Features Of Hmgb1mentioning
confidence: 99%